Implementation of folk games ethnomathematics in mathematics learning: A systematic literature review - Monica Priska Aprilia Winardi; Al Jupri (Universitas Muhammadiyah Malang, 2025)
This research is a Systematic Literature Review (SLR) that aims to find out what ethnomathematics can be found in traditional games and how traditional game ethnomathematics is implemented in mathematics learning. The urgency of this research lies in examining ethnomathematics embedded in traditional games as a means to preserve cultural heritage and introduce innovative, contextual, and meaningful approaches to mathematics learning, thereby enhancing students’ motivation, creativity, and academic performance by linking mathematical concepts to their cultural backgrounds. Findings from this SLR are expected to outline research trends in the field and offer recommendations for more effective strategies in implementing culture-based mathematics education. The inclusion criteria are as follows: (1) articles and proceedings published in the period 2015-2025; (2) articles and proceedings used have been published in international journals indexed by scopus; (3) studies in the articles discuss about ethnomathematics in folk games from Indonesia. The results of this research show that several traditional games in Indonesia that contain mathematical concepts include the games namely endog-endogan, engklek, ligu, rimau/dam-daman, guli/ekar/marbles, pacu jalur, tong tong galitong ji, and bekel.. The implementation of ethnomathematics in traditional games to mathematics learning has had a positive impact, including reducing students' difficulties in understanding a concept, as well as improving learning outcomes, improving students' understanding of the material/concept of creative thinking skills, improving character values, improving mathematical connection skills, and making the more interesting and meaningful learning.